ZB-16, a Novel GPR119 Agonist, Relieves the Severity of Streptozotocin–Nicotinamide-Induced Diabetes in Rats - Tyurenkov, Ivan N.; Kurkin, Denis V.; Bakulin, Dmitry A.; Volotova, Elena V.; Chafeev, Mikhail A.; Smirnov, Alexey V.; Morkovin, Evgeny I. (Frontiers in Endocrinology, 2017)
GPR119 is involved in the regulation of incretin and insulin secretion, so the GPR119 agonists have been suggested as novel anti-diabetic medications. The purpose of this work was to assess the influence of novel GPR119 agonist ZB-16 on the glucose utilization, insulin and GLP-1 secretion, and the morphology of pancreas in rats with streptozotocin-nicotinamide-induced diabetes. 45 male Wistar rats were used in the study. The criteria of streptozotocin-nicotinamide-induced diabetes were blood glucose levels 9-14 mmol/l measured in fasting conditions on the 3rd day since administration of streptozotocin (65 mg/kg) and nicotinamide (230 mg/kg). Animals failed to reach the criteria were excluded from the experiment. The substances were administered per os once per day for 28 days. Measurements included blood glucose monitoring (every 7 days), glucose tolerance test (every 14 days), the assessment of insulin and GLP-1 levels in blood plasma (28 days after beginning) and the results of immunohistochemical staining of pancreas. It was found, that ZB-16 (1 mg/kg per os, once a day) decreases the blood glucose levels under fasting conditions and improves the glucose utilization. These changes were associated with the increase of stimulated secretion of GLP-1 and insulin, accompanied by the growth of insulin-positive cells in pancreas. Thus, ZB-16 could be a promising anti-diabetic drug for oral administration.